BMS458: Quantitative Methods for Biology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2018)
This is an elementary course in biological data analysis. The course is design to equip students with the necessary analytical knowledge and tools in pursuance of their studies in biological sciences. The topics covered are basic probability theory; probability distributions – normal, binomial and Poisson; elementary sampling theory; estimation and hypothesis testing and the analysis of variance. The emphasis is on the laboratory sessions, where students will learn to formulate testable hypotheses, design a scientifically sound experiment, conduct the experiment and analyze the data using the methods taught in the lectures.